2020
DOI: 10.34188/bjaerv3n3-020
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade física e fisiológica de sementes de cártamo submetidas ao beneficiamento em mesa de gravidade

Abstract: The use of alternative crops in the off-season becomes interesting in the rotation system this system provides breaking of disease cycles, assisting in the control of weeds and insects. Safflower culture meets these precepts for use in this way in the state of Rio Grande do Sul, as well as assisting on the decompression and translocation of nutrients in the soil, as the root system can reach up to two meters deep. The experiment was constituted by 40 treatments, involving two factors: factor Aeight lots of saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Félix et al (2017) stored Adonidia merrillii seeds found that seedling length had a progressive decrease with the advancing storage period, confirming the results of this study. Macedo et al (2020) evaluated the physical and physiological quality of safflower seeds submitted to processing in a densimetric table and identified that the total seedling length may be related to seed density, specific mass, and thousand-seed mass.…”
Section: Resultsmentioning
confidence: 99%
“…Félix et al (2017) stored Adonidia merrillii seeds found that seedling length had a progressive decrease with the advancing storage period, confirming the results of this study. Macedo et al (2020) evaluated the physical and physiological quality of safflower seeds submitted to processing in a densimetric table and identified that the total seedling length may be related to seed density, specific mass, and thousand-seed mass.…”
Section: Resultsmentioning
confidence: 99%